Radical Reflection: Toward the Transformation of Everyday Teaching and Learning in English Composition - (:unkn) unknown (My University, 2014)
Education is a necessary component in the emancipatory transformation of current capitalist society, with its exploitative social relationships, to one which is based on promoting and supporting human growth and potential. A libertarian education, as Paulo Freire writes of it, "must begin with the solution of the teacher-student contradiction, by reconciling the poles of the contradiction so that both are simultaneously teachers and students" (Pedagogy of the Oppressed 59). An additional impediment to developing education useful for this transformation is the separation of thought from action in educational theory and practice. The field of composition studies similarly operates according to its tendency to separate reflection from writing. While I find that compositionists intuitively know that reflection and action are best theorized as inseparable, our practices tend to separate theory from practice, writing from action, teachers from students, epistemology from ontology. This dissertation is an extended consideration of what might result if we truly took seriously how thought and action (epistemology and ontology) can not and should not be separated and to posit a composition course that can support the conditions of this transformed (unified) relation between these dichotomized parts of our existence. I ground this consideration in an examination of reflection as conceived in composition studies which, in its theoretical and applied treatments of reflection, often employs the dichotomy. In order to rethink reflection in composition studies so that it is unified with action and writing, I argue for a deliberate refocusing of the field's attention toward enacting physical/institutional change, attention which is inordinately given to theorizing language and the power of rhetoric. The human agency in our social structures necessary for emancipatory change is enacted through the dialectical linking of this dual attention to conditions/structural change and language/power. My understanding of this dialectical necessity begins with Karl Marx's unified theory of consciousness, which does not separate thinking from action, and traces its development through the 20th and 21st century theorists who have also drawn upon it in efforts to effect emancipatory change.
Keywords: Composition; Education; Instruction; Reflection; Studies; Writing